The influence of brain respiration on interpersonal emotion regulation in young adults - Efnie Indrianie; Meta Dwijayanthy (Institute of Computer Science (IOCS), 2025)
This study aimed to determine the effect of Brain Respiration on the Interpersonal Emotion Regulation (regulating emotions independently, without others present) in young adults experiencing romantic problems. Through Brain Respiration, a person can manage emotional functions, reduce stress, and stay comfortable even when interpersonal support is not always available. Thirty young adults participated in this study. Fifteen young adults in the experimental group received Brain Respiration, whereas the rest in the control group did not. The degree of interpersonal emotion regulation was measured using the Interpersonal Emotion Regulation Questionnaire (IERQ). The results showed a decrease in the degree of interpersonal emotion regulation among young adults in the experimental group after receiving Brain Respiration. This can be seen in P(T<=t) two-tailed, which is 4.13985E-11 < alpha 0.05, and the average degree of interpersonal emotion regulation from 88.13 to 77.73. There was also no difference in the degree of Interpersonal Emotion Regulation in young adults in the control group without Brain Respiration (P(T<=t) two-tailed was 0.120590511 > alpha 0.05), and the average degree of Interpersonal Emotion Regulation in the pre- and post-tests was 85.6 and 85.8.